Fortunes et infortunes du précepte horatien utile dulci dans la littérature française : essai d’interprétation du Classicisme à la Modernité - José Manuel Losada (Çédille: Revista de Estudios Franceses, 2019)
Drawing on four famous verses of Horace’s Epistle to Pisones (v. 333-334 and 343-344), criticism and literary practice transformed the poet into a benefactor of humanity who improves men by instructing and entertaining them. Our goal is to reveal―as in filigree and marking the transition from one era to another, from classicism to modernity―the deviations to which these verses have given rise.